Self-plasticizing membrane based on Co(II)-porphyrin modified with silver nanoparticles for thiocyanate detection - Zainal, Siti Nuraqidah; Rezayi, Majid; Alias, Yatimah; Mahmud, Habibun Nabi Muhammad Ekramul (MYU K.K., 2019)
A novel potentiometric anion-selective self-plasticizing polymeric membrane based on 5,10,15,20-tetrakis-(4-methoxyphenyl)-21H,23H-porphyrin cobalt(II) (CoTMeOPP)-silvernanoparticle- modified glassy carbon electrode (GCE) was examined for use in the detection of thiocyanate anions. The membrane was characterized by X-ray diffraction (XRD) analysis, field-emission electron microscopy, UV-visible diffused reflectance spectroscopy, and fluorescence spectroscopy. The prepared ion-selective sensor exhibited a positive Nernstian response and deviated from the classical Hofmeister selective pattern with a significantly sensitive and enhanced response towards the thiocyanate anion. It exhibited a rapid response of 3 s with a low detection limit of 9.55 × 10-8 M within the concentration range from 1 × 10-1 to 1 × 10-7 M. The sensor also showed a high selectivity for the thiocyanate anion over a variety of anions. The influence of the additives was studied and this sensor was successfully applied to the potentiometric titration of silver nitrate and the direct determination of the amount of thiocyanate anions in a wide array of samples of river water, ex-mine lake sediment, human saliva, and fish.